128 Progress and early outcomes of a cardiometabolic clinic in a uk tertiary cardiology centre. (6th June 2022) - Narain, Rajay; Bijman, Laura; Chen, Mimi
Abstract : Introduction: Diabetes mellitus confers a two-fold risk of adverse cardiovascular (CV) outcomes and up to four-fold risk of heart failure (HF). Cardiovascular outcome trials (CVOT) have demonstrated that new classes of antidiabetic drugs confer beneficial effects on cardiovascular (CV) including heart failure (HF) outcomes and cardiometabolic risk factors such as adiposity. International guidelines have been updated accordingly to reflect ongoing publication of evidence. However changes in prescribing practice have been limited by clinical inertia and limitations on patient encounters and resources, exacerbated by the covid-19 pandemic. 1, 2, 3, 4 The cardiometabolic clinic (CMC) at St. George's University Hospitals NHS Foundation Trust (SGH) facilitates the optimisation of medications and lifestyle interventions to reduce cardiometabolic risk via multidisciplinary review by a cardiologist and diabetologist. Purpose: To describe the activity, interventions, and clinical impact of the CMC. Methods: Patient investigations and observations and clinical documentation were reviewed retrospectively over a 36-month period (29/09/2020 to 14/03/2022). Results: A total of 174 patients were seen up to and including 14/03/2022.Of patients seen, 71 have been booked for follow up appointments, 98 discharged, 86 referrals have been made to other specialties.In addition to discussion of modifiable risk factors with each patient, numerous successful pharmacological interventions have been made (Table 4). 28 medications were stopped due to contraindication, adverse effects or to permit optimisation of evidence-based treatments.Among the 107 patients in whom antidiabetic drugs have been initiated or titrated, a reduction in HbA1c has been observed in 40 (mean -18 mmol/mol) and a reduction in fructosamine in one patient (-39 umol/L) while for 14 patients HbA1c incidentally increased (mean +7 mmol/mol).Weight loss has been reported thus far in 18/ 88 patients initiated or optimised on SGLT2 inhibitors, 7/27 on metformin, and 12/ 19 on GLP-1 agonists. SGLT2 inhibitors were stopped in 3 patients due to intolerance or contraindication: one due to increased urinary frequency and two due to renal impairment. One male patient reported a urinary tract infection which was treated. No serious adverse effects were reported.Of 103 CMC patients on SGLT2 inhibitors, 8 had further HF-related hospitalisations. Of the 6 patients referred by the bariatric team due to high risk for surgery on account of cardiac disease or diabetes, all have cancelled or delayed proceeding with bariatric surgery.Availability of clinical outcomes is limited by the short period of follow up thus far. Notably, these interventions have been achieved whilst delivering CMC virtually due to the ongoing covid-19 pandemic. Conclusion: The CMC is a novel integrative approach to optimising management of cardiometabolic risk and incorporation of evidence-based cardiometabolic medications. As risk of morbidity and mortality due non-communicable diseases intensifies in an increasingly comorbid population and in the context of a resource-strained health service, efficient care models such as the CMC are an important enterprise to address cardiometabolic risk and disease. As this clinic expands its service, it will continue to serve as example for comparable innovation in other centres. Conflict of Interest: None